"Our war every day" History, violence and critical thinking in Ignacio Martín-Baró - Gómez Lacayo, Juan Pablo (2021)
The Central American wars of the 1980s caused analytical twists in intellectual agendas. In this work, I study the case of Ignacio Martín-Baró, social psychologist and Jesuit priest from the Central American University (UCA) of El Salvador. I postulate that his proposal to print a Latin American perspective on psychosocial thought derived from the need to understand the social crises that arose with the war. Martín-Baró became interested in the ‘torn world of daily life’ as a place for analyzing the main social conflicts, among which he highlighted torture and the high dose of cruelty manifested in the exercise of violence. Finally, I analyze his reflections on the impact of the war on mental health, especially in childhood, and underline their call for attention on the cultural nature of violence and the challenges that this implies for the imagination of a new future of coexistence. Although he was a thinker in constant alert about the importance of historically supported analysis to understand social crises, his intellectual interventions imagined a future of historical viability and sustainability of life for the majorities with whom he committed his work.